Basic Needs Insecurity Among First-Generation Community College Students With Disabilities During the COVID-19 Pandemic. Issue 1 (2nd January 2023) - Soria, Krista M.
ABSTRACT: The purpose of this study was to examine whether first-generation students with disabilities at community colleges experience different rates in food and housing insecurity compared to their peers during the COVID-19 pandemic. First-generation students with multiple disabilities, a psychological disorder, another disability or medical condition not offered in the survey, and chronic illness had increased odds of experiencing food and housing insecurity; first-generation students with physical disabilities and cognitive, learning, or neurological disorders or disabilities had increased odds of experiencing food insecurity; and continuing-generation students with multiple disabilities also had increased odds of experiencing food and housing insecurity.